SPIRITUALITAS SOSIAL DAN BUDAYA JAWA DALAM MEMBANGUN WISATA DESA: STUDI KASUS DESA NGAWONGGO, JAWA TIMUR - Mahatva Yoga Adi Pradana (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2025)
The research aims to find propositions in linking aspects of spirituality with the social environment. This action is carried out on the model of the development of tourist destinations in Javanese culture. Tourists have an important role in running the tourism village business sector. This behavior is certainly based on patterns and actions in regulating the mechanism of running village tourism. The existing form of village tourism makes tourists must have interesting characteristics to survive. Until finally this form of tourism development follows the approach of Javanese tradition by emphasizing attitudes that are supported by spirituality. This research uses a qualitative approach, by conducting in-depth interviews with tourists. Tourists have mental strength in making traditions a model of tourism development. Various motives and benefits have been obtained by tourists. Until researchers found a pattern of relationships that make this tour develop quickly during the Covid-19 pandemic. Thus, the results obtained in this study are expected to make a theoretical contribution related to the model of tourism village development that has strong Javanese cultural characteristics. Social spirituality becomes a bridge in the realm of thought of tourists in moving the values of religion then implemented in the development of social values. To give rise to a new concept in interpreting the thoughts of tourists and social actions carried out. In addition, researchers also get three values of social spirituality used, namely, Trust, Believe, and Sincere.